Social cognition and Relevance: How stereotypes impact the processing of definite and indefinite descriptions - Mari, Magali A.; Müller, Misha-Laura (Frontiers in Communication, 2023)
This paper focuses on the impact of social cognition on the processing of linguistic information. More specifically, it brings some insights to Relevance theory’s construal of MeaningNN (Sperber and Wilson 2015), which seeks to account for non-propositional meanings (Wilson 2016). It shows, through two experiments, how gender and nationality-related stereotypes guide the processing of definite and indefinite descriptions. Experiment 1 consists of a self-paced reading task (with 59 French native speakers), introducing information confirming vs violating gender stereotypes within a nominal phrase (NP). The NP (e.g., “chirurgien/chirurgienne”, “surgeonmale/female”) was itself introduced either by a definite article (presupposition) or an indefinite article (assertion). Results showed that information violating gender stereotypes was costlier to process than stereotype-congruent information. Moreover, when information violated gender stereotypes, definite descriptions became significantly costlier than indefinite ones, because they required the identification of a salient referent which contradicted stereotypical expectations. Experiment 2 tested the effects of definite vs indefinite NP on processing nationality-related stereotypes in a self-paced reading task (with 49 French native speakers). Participants read definite vs indefinite NPs referring to representatives of a country. The NP was subsequently paired with information that confirmed vs contradicted nationality stereotypes. Results showed that information contradicting nationality stereotypes were significantly costlier to process than information confirming stereotypes. Furthermore, when information contradicted nationality stereotypes, indefinite descriptions (which promote a single occurrence reading) failed to facilitate information processing compared to definite descriptions (which promote a generalized representation of the social category). Overall, the present findings are consistent with research on stereotypes, in that they show that stereotype-incongruent information affect sentence processing. Importantly, while Experiment 1 revealed that stereotypes affected the processing of linguistic markers, Experiment 2 suggested that linguistic markers could not modulate the processing of stereotypes.